THE NECESSITY OF PUBLIC-PRIVATE PARTNERSHIPS IN THE DEVELOPMENT OF THE DIGITAL ECONOMY - V. Parakhina; R. Ustaev; O. Boris; G. Vorontsova; O. Momotova (Вестник Северо-Кавказского федерального университета)
The article substantiates the impossibility of expanding the strategic opportunities of socioeconomic development of the country without changing the technological structure and full compliance with the global trends of scientific and technological development. The analysis of the development of digital technology in Russia and abroad. It is shown that the use of public-private partnership (PPP) in the conditions of digitalization of the economy has, with its own peculiarity, the creation of information systems, virtual models, open information portals reflecting the promotion of PPP projects along the stages of their life cycle and their relationship with stakeholders. The main limiting factors of effective implementation and development ofjoint significant projects with the participation of the state and business on the terms of mutually beneficial cooperation are given. The main priority directions of development of modern economy are deined.